1950s : Works on Paper - Boyanoski, Christine (Toronto : Art Gallery of Ontario, 1988)
Bobak, Bruno ; Shadbolt, Jack ; Newcombe, William ; Cahen, Oscar ; Bush, Jack ; Ronald, William ; Mead, Ray ; Nakamura, Kazuo ; Eskowitz, Gebshon ; etc.
1950s : Works on Paper, Laurentian University Museum and Art Centre, Sudbury, October 13 - November 13, 1988 ; Chatham Cultureal Centre, Chatham, January 20 - March 1, 1988 ; Travelling Exhibition
English
kunstcatalogus